UNDERGRADUATE STUDENTS PERCEPTIONS ON EXTENSIVE READING STRATEGY IN VOCABULARY CLASS - Wijaya, Kristian Florensio (PROJECT (Professional Journal of English Education), 2020)
AbstractVocabulary is one of the essential elements of English Language Teaching. It is therefore important to ensure that the students are able to obtain sizable vocabulary knowledge during their academic performance. Extensive reading strategy played a major role in that process. Two research problems were proposed in this study. The first is to know the effectiveness of extensive reading strategy in vocabulary class. The second is to discover the significant improvement of English Language Education students’ vocabulary knowledge through extensive reading strategy. In this qualitative study, three research instruments: observation, classroom survey, and focus group discussion were employed. Qualitative content analysis was implemented to draw meanings out of the data gathered. Five major findings were as follows: (a) ELESP students viewed vocabulary as an important element in English language mastery (b) Loved reading extensively (c) Had limited time to read (d) Lose their reading motivation easily (e) Suggested regular checking of vocabulary books.Keywords: vocabulary, extensive reading strategy, qualitative content analysis